Review of BRICS regulatory practices in the field of drugs compounding - D. S. Yurochkin; D. D. Mamedov; S. E. Erdni-Garyaev; A. V. Yarutkin; V. L. Bagirova; P. S. Guryanov; O. Loudiyi; W. Li (Фармация и фармакология (Пятигорск))
In the formation of a common market within the framework of interstate associations (Unions), the goal of improving the health of the member states population can be achieved, among other things, by providing an unimpeded access to safe, effective and quality medicines (drugs). One of the elements is activities in the field of these medicinal products  compounding. This review has been prepared by authors due to the lack of information in the Russian-language literature  on the regulation of this area in the current legal systems of the BRICS countries.The aim of the work was to analyze the regulatory mechanisms and current approaches to the organization of activities in the field of medicinal products compounding, presented in the legislation of the BRICS interstate association (Union) member countries, including their structuring (systematization) in order to develop proposals for the convergence of these practices.Materials and мethods. PubMed, Google Scholar, elibrary.ru, and specialized databases of regulatory legal documents of the BRICS countries were used as search resources. The following keywords were used as search keywords: “drug”, “drug product”, “medicinal products compounding”, “pharmacy organization”, “medical organization”, “compounding”, “drug preparation”, “drug dilution (reconstitution)” in English, Portuguese, Spanish, Chinese and Arabic. The paper uses empirical, theoretical, quantitative tools, including the analysis of a wide list of relevant sources - regulatory legal documents governing the activities of compounding pharmacies in the BRICS countries.Results. The study presents key regulatory legal acts and documents, analyzes them and describes the main provisions of the legislative framework for the organization of activities in the field of medicinal products compounding. The identified peculiarities determine the need to rethink the current state of the Russian regulation of the medicinal products compounding sector. The study emphasizes the need to improve regulatory approaches in Russia. The BRICS countries can strive to develop the best practices and “gold” standards for the organization of this socially important activity in the field of medicinal products compounding. Such an approach can led to the creation of a unified good practice in compounding and dispensing of medicinal products. Conclusion. The authors of the study consider it advisable to carry out a further and more detailed elaboration of the convergence issues of regulatory practices of both health care systems and pharmaceutical industries in the BRICS member states. It has been proposed to develop and form a “Roadmap” (an action plan) for the development of the cooperation between the BRICS member states in the field of health care and pharmaceutical industry in order to intensify integration processes and build a modern model of the public health and drug market, including joint research and development by world-class scientific centers for technological development of the interstate association (Union) countries.